Malem Selasan Activity as A Strategy of Islamic Education Through Nadzom Fiqih (Fasholatan) in the Community of Ngrukem Bantul - Azizah, Siti Nur; Muhtarom, Hadi (YASIN, 2024)
As a santri village, Ngrukem village, Bantul, Yogyakarta needs to continue to develop various activities, both social, religious, and other activities, in order to improve the quality of its people. This research aims to determine the strategy of Islamic education through the Fiqih Fasholatan activities in Ngrukem Sewon Bantul village with the media Nadẓom Fiqih (Fasholatan) by KH. Nawawi Abdul Aziz. The researchers used qualitative research to understand this phenomenon. The subjects in this research were the Nadzom Fiqih presenters and the Ngrukem village community, who participated in the evening prayer activities. At the same time, the object of the research focused on the evening prayer activities that studied Nadzom Fiqih in Ngrukem Sewon Bantul Yogyakarta. The research results indicate that the evening prayer activities in Ngrukem village have a significant impact on the community of the Ngrukem regarding Islamic education, especially in the study of Fiqih Fasholatan. There are several approaches to Islamic education used for the community, namely a humanitarian approach, a participatory approach, a collaborative approach, a sustainable approach, and a cultural approach. Not only that, this activity has two critical impacts, namely educational impact and social impact on the community.